1983
DOI: 10.1136/adc.58.6.438
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anaemia with hypoproteinaemia.

Abstract: SUmmARY Forty two children were admitted to this hospital between 1975 and 1980 with severe iron deficiency anaemia and 8 of them also had oedema caused by a low concentration of serum proteins. These 8 patients, aged 8-24 months, and 13 age matched controls were investigated. The patients had excessive faecal loss of 59FeCl or 51Cr-albumin, or both; their jejunal biopsy specimens showed little decrease in the ratio of villous height to crypt depth; and they had fewer intraepithelial lymphocytes and cells cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 18 publications
1
51
0
Order By: Relevance
“…Dietary iron deficiency was also thought to be primary in other studies that showed malabsorption of sugars (67) or of iron itself (68) because the abnormalities could be corrected by treatment with iron. A similar response to treatment has also been observed in the relatively rare cases of iron deficiency anemia accompanied by hypoproteinemia (69,70).…”
Section: Differences In Organ Susceptibilitymentioning
confidence: 51%
“…Dietary iron deficiency was also thought to be primary in other studies that showed malabsorption of sugars (67) or of iron itself (68) because the abnormalities could be corrected by treatment with iron. A similar response to treatment has also been observed in the relatively rare cases of iron deficiency anemia accompanied by hypoproteinemia (69,70).…”
Section: Differences In Organ Susceptibilitymentioning
confidence: 51%
“…However, in infancy and in early childhood, nutritional iron de ciency remains a problem in the absence of related other diseases, mainly in patients of Southeast Asian ancestry (14,15). Increased intestinal blood loss is associated with iron de ciency in mucosal damage due to cow's milk intolerance in infants (16,17). In Finland, parasitic infections such as giardiasis are basically non-existent, and in cases of coeliac disease, a common cause of malabsorption in our country, usually only a mild anaemia is observed.…”
mentioning
confidence: 99%
“…PLE has been previously reported in association with IDA [3][4][5][6][7][8][9][10][11]. In many cases, excessive milk intake (>30 oz./day) has been noted [5,6,8] and is suspected to directly cause enteropathy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients with milk protein allergy have been shown to have gastrointestinal protein losses [12,[19][20][21] and white cell infiltrates in the intestinal mucosa [12,22,23]. In a study of eight patients with PLE and IDA who did not have a positive test for celiac disease or milk protein allergy, however, intestinal biopsies revealed no evidence of mucosal damage and normal numbers of intestinal intraepithelial lymphocytes [6], suggesting PLE and IDA can occur together without primary gastrointestinal pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation